Korelasi Self-Esteem dengan Perilaku Narsistik pada Pengguna Media Sosial - Anjani, Azzahra Primadivta; Sulistyowati, Arlina Dhian; Khayati, Fitriana Noor; Sawitri, Endang; Supardi, Supardi (TRIAGE Jurnal Ilmu Keperawatan, 2025)
Narcissistic tendencies or also called Narcissistic Personality Disorder (NPD) occur due to a person's attitude or behavior that excessively creates excessive fantasies about themselves. In 2023, the Ministry of Health of the Republic of Indonesia reported a 12% increase in personality disorder cases, including NPD, compared to the previous year, with most cases identified among young individuals who were actively engaged in social media use.People who have narcissistic tendencies have a high intensity of social media use. The purpose of this study was to determine the relationship between self-esteem and social media NPD behavior in students of the Health Study Program, Muhammadiyah University of Klaten. This study used quantitative with the Cross-sectional method. The sampling technique in this study used Stratified Random Sampling. The sample in this study was 161 respondents of Level 1 Health Study Program students, Muhammadiyah University of Klaten. The data collection tool in this study used a questionnaire on self-esteem and a questionnaire on NPD. The statistical test in this study used the Spearman rank. The results of this study indicate that most students have a level of self-esteem in the moderate category with a percentage of 41.51% or 66 people, the majority of respondents showed a level of NPD in the moderate category with a percentage of 35.85% or 57 people. Shows that there is a significant and positive relationship between self-esteem and NPD behavior with a p-value of 0.00 <0.05, with a correlation value of 0.405, which is in the medium category, meaning that the higher the student's self-esteem, the greater the tendency for narcissistic behavior on social media